Micro perspective of tourism and hospitality - Cruz, Zenaida Lansangan (Manila, Philippines : Rex Book Store, 2019)
Micro perspectivr of tourism and hospitality is an introducory book for students taking tourism and hospitality courses. This book describes the working, operations, and integrative activities of major stakeholders in the tourism and hospitality industry ; provides an in-depth study of the nature and distinctive characteristics of each sector of the entire tourismindustry focusing on the management, organization, and planning of businessstrategies for various entities in the local setting ; analyzes the posisible impacts of external factors and trends on the different industry sectors ; explains client profiling and travel motivations ; discusses the management and marketing of service-oriented business organizations ; and identifies the employment opportunities available in each sector and the corresponding qualifications for the jobs. THis book follows an outcome-based approach, with learning outcomes presented at the beginning of each chapter, a summary, discussion questions, chapter activities, and a chapter quiz at the end of the chapter.
1. The Psychology of tourism -- 2. The Sociology of tourism -- 3. Tourism -- 4. Transportation sector -- 5. Accommodations -- 6. Food and beverages sector -- 7. Recreation and leisure -- 8. Tourist attraction and theme parks -- 9. The MICE industry : meaning and importance -- 10. Tourism marketing -- 11. Tourism promotion -- 12. Tourism distribution channel -- 13. Tourism planning -- 14. Tourism development -- 15. Employment opportunities and qualifications in the tourism and hospitality industry.
Includes bibliographical references and index.
Keywords: TOURISM -- MANAGEMENT